CONDITION of Hoplias aff. malabaricus (BLOCH, 1794) IN TWO COASTAL STREAMS of ITANHAEM RIVER BASIN, BRAZIL - de Sant'Anna, Evandro Bonocchi [UNESP]; Goitein, Roberto [UNESP] (Inst Pesca, 2009)
The main purpose of this research was to measure the condition of the fish species Hoplias aff. malabaricus collected in Aguapeu River (black waters) and Branco River (white waters), which belong to Itanhaem River basin, a coastal watershed in São Paulo state, Brazil. Individuals of Hoplias aff. malabaricus were sampled by using gill nets, monthly from March 2001 to February 2002. The Condition Factor was obtained through the length-weight relationship, assuming that the higher the mass for a given length, the better the condition of the fish. The Condition Factor was compared among fishes from both rivers, resulting that Branco River individuals have significantly lower condition. Limnological aspects were studied from May 2001 to November 2002 and some show significant differences between Aguapeu River and Branco River. These were salinity, do and total organic N, which the higher values being observed in Branco River propably due to estuarine waters influence. However, the lower condition of the Branco River fishes should also be an effect of a disturbance due to the sand mining in this river, since this activity cause important alterations to the environment, affecting the whole biota, included aquatic macrophytes, invertebrates and fishes.
Keywords: Hoplias aff. malabaricus; condition factor; Aguapeu River; Branco River; Itanhaem River; aquatic macrophytes; sand mining